Testosterone down-regulates expression of αvβ3-integrin, E-cadherin and mucin-1 during uterine receptivity period in rats - Helmy Mohd Mokhtar,; Nelli Giribabu,; Naquib Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Adequate development of uterine receptivity is crucial for establishment of pregnancy. Expression of uterine receptivity molecules i.e. αvβ3 integrin, E-cadherin and mucin-1 could be affected by testosterone. The objective of this study was to investigate effect of testosterone on expression of these molecules during early pregnancy. 30 ovariectomised female Sprague-Dawley rats were divided into 5 groups that consisted of vehicle control, rats received eight days sex-steroid replacement regime (intended to mimic the hormonal changes in early pregnancy) and three groups of rats given testosterone (1 mg/kg/day) subcutaneously with or without flutamide or finasteride between day 6 and 8 representing the period of uterine receptivity. At the end of the treatment, rats were sacrificed and uteri were removed. Expression and distribution of αvβ3 integrin, E-cadherin and mucin-1 were examined by immunoflourescence and levels of messenger RNA (mRNAs) were evaluated by real-time PCR. Expression of αvβ3 integrin, E-cadherin and mucin-1 in the uteri of rats receiving sex-steroid replacement regime increased significantly as compared to control (p<0.05). In these rats, concomitant administration of testosterone between day 6 and 8 resulted in expression of αvβ3 integrin, E-cadherin and mucin-1 to decrease significantly (p<0.05) as compared to rats receiving sex-steroid replacement regime without testosterone treatment. Moreover, the testosterone effects were not antagonized by either flutamide or finasteride. As a result, reduced expression of uterine receptivity molecules by testosterone might interfere with early pregnancy establishment, therefore could adversely affect the female fertility.